Text Data Compression Software Design Using Arithmetic Coding Method - Al Aris (Cattleya Darmaya Fortuna, 2020)
Data compression is the science or art of representing information in a more compact form. Various algorithms have been developed for data compression purposes. One of the algorithms used is Arithmetic Coding. The working principle of this algorithm is to replace a series of input symbols with floating point numbers, where the longer and more complex the encoded message, the more bits required for file compression. This software is designed using the Visual Basic 6.0 programming language and is able to compress text files with a compression rate of about 75 percent. This system can also be used to compress two or more text files at once.